PERANCANGAN SISTEM PENDUKUNG KEPUTUSAN UNTUK MENENTUKAN NILAI TERBAIK SISWA DENGAN METODE TOPSIS PADA AHA MUSIC COURSE - Zahro, Fatimah; Saputra, Suranto; Hermawan, Rudi (Bapelitbang Kabupaten Batang, 2023)
in the digital era like today, there are many updates Information to students through the website to make it easier to see through cellphone or computer. Value is a point of achievement in the learning process of each student.Through the value of students can measure how high the achievement has been learned over time learning. Music school requires a system to facilitate teachers to calculate student assessments at each meeting as the measuring point of the student can already be declared passed or not next level Assessment of the best students currently running at the company studied by entering values manually on paper because of the limited computer equipment for teachers and the large number of students,each instrument represents one teacher for data collection the value of each student is the best so this method is not objective because not all data according to the value and number of meetings that exist. For To solve this problem, the Topsis method is used. It is hoped that using this method can solve the problem of determining the best student scores in the AHA Music Course.